2012
DOI: 10.5402/2012/938974
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation: The Void in the Management of Anterior Cruciate Ligament Injuries—A Clinical Review

Abstract: The rehabilitation of patients undergoing anterior cruciate ligament (ACL) reconstruction requires symmetry in bilateral quadriceps strength and adequate proprioception capabilities prior to return to preoperative level of activity or sport. This is the limiting factor and can delay the time that patients can return to play. There is little literature on pre-operative physiotherapy or prehabilitation of patient with ACL injury. This paper discusses the anatomy, biomechanics, surgical decision making, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 121 publications
(129 reference statements)
3
12
1
Order By: Relevance
“…Internal knee injuries account for nearly 45% of sports related injuries, with anterior cruciate ligament injury being the most prevalent structure damaged 1 . Anterior cruciate ligament injury is associated with pain, instability of the joint, muscle weakness, functional limitation, poor quality of life, and an increased risk of knee-related osteoarthritis 2,3 . Anterior cruciate ligament reconstruction surgery is the main treatment for anterior cruciate ligament injuries 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal knee injuries account for nearly 45% of sports related injuries, with anterior cruciate ligament injury being the most prevalent structure damaged 1 . Anterior cruciate ligament injury is associated with pain, instability of the joint, muscle weakness, functional limitation, poor quality of life, and an increased risk of knee-related osteoarthritis 2,3 . Anterior cruciate ligament reconstruction surgery is the main treatment for anterior cruciate ligament injuries 4 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Anterior cruciate ligament injury is associated with pain, instability of the joint, muscle weakness, functional limitation, poor quality of life, and an increased risk of knee-related osteoarthritis. 2,3 Anterior cruciate ligament reconstruction surgery is the main treatment for anterior cruciate ligament injuries. 4 Over 200 thousand anterior cruciate ligament reconstruction surgeries take place each year in the United States, which costs more than $3 billion annually.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have shown that prehabilitation prior to orthopedic surgery accelerates the return to normal physical function, potentially hastening the capacity to return to work. 20,24,27 Similar to patients with stable coronary artery disease with or without stable angina, patients awaiting orthopedic surgery could join classes of aerobic exercise training as well as resistance training to increase their CRF prior to surgery and thus improve their prognosis. In addition, it has previously been shown that continuous and interval training were equally effective in patients with coronary artery disease.…”
Section: Strategies To Improve Fitness Prior To a Surgical Or Other I...mentioning
confidence: 99%
“…15,16 Enhancing physical function through perioperative exercise programs has been demonstrated to improve outcomes among patients undergoing both cardiac and noncardiac surgery, including hepatic transplantation, lung cancer resection, abdominal aortic aneurysm (AAA) repair, upper gastrointestinal surgery, intra-abdominal surgery, bariatric surgery, and coronary artery bypass grafting (CABG). [8][9][10][11][12][13][14][17][18][19][20][21][22][23][24][25][26][27][28] Some notable studies in this area along with key results are outlined in Table 1. 22,[29][30][31][32][33][34][35][36][37][38] Note that the application of prehabilitation to cardiac and pulmonary rehabilitation is relatively recent, and the benefits of prehabilitation have been shown to apply across the spectrum of chronic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation